The spiritual character of Pole Attempt of a philosophical portrait - Andrzejewski, Bolesław (Folia Philosophica, 2017)
The article deals with the history of Polish philosophy. Particular attention is given to its practical, at times even pragmatic overtone. The praxis dominates in the Middle Ages, modern philosophy and also in contemporary thought. After the appearance of Kantianism, there emerges in Poland a theoretical consciousness. These practical and theoretical dimensions lead to a synthesis that is referred as “Polish humanism”.